2017
DOI: 10.1094/pdis-12-16-1784-re
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping Sunflower Genetic Resources for Sclerotinia Head Rot Response: Assessing Variability for Disease Resistance Breeding

Abstract: Sclerotinia head rot (SHR) is one of the most serious constraints to sunflower (Helianthus annuus L. var. macrocarpus) production worldwide. Here, we evaluated the response to SHR in a sunflower inbred panel from a large INTA germplasm collection, consisting of 137 inbred lines (ILs). Field trials were performed over five consecutive seasons using a twice-replicated randomized complete-block design. Disease incidence, disease severity, incubation period, and area under disease progress curve for disease incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 35 publications
3
24
1
Order By: Relevance
“…Filippi et al . [ 30 ], who studied SHR resistance with association mapping in the same location, also observed that the DI and DS values were below the overall mean in an assay conducted in 2011/2012. In agreement with our findings, Abawi and Grogan [ 66 ] found a negative correlation between temperature and SHR disease levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Filippi et al . [ 30 ], who studied SHR resistance with association mapping in the same location, also observed that the DI and DS values were below the overall mean in an assay conducted in 2011/2012. In agreement with our findings, Abawi and Grogan [ 66 ] found a negative correlation between temperature and SHR disease levels.…”
Section: Discussionmentioning
confidence: 99%
“…These values are comparable to those obtained by Filippi et al . [ 30 ] using the same approach. The moderate h 2 values suggest that marker assisted selection, using either the AM or the BMP approach, may be the method of choice when breeding for resistance to SHR, instead of conventional phenotypic selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These distinct groups of accessions are of particular interest when planning the incorporation of new genetic backgrounds to each breeding collection. Among them, STRUCTURE group 4 contains a mixture of Argentinean HA and RHA inbred lines, bred for traits of agronomic importance such as drought stress tolerance and rust and sclerotinia head rot resistance [4,5,45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a relationship between the values of genotypic variance and those of the phenotypic variance for RIP. In Argentina, Godoy (2001) detected that the genotypic contribution to phenotypic variance in the 49 hybrids evaluated in two localities of southeastern Buenos Aires was of 67%, whereas Filippi et al (2017) showed a contribution of 0-48% (annual) and of 11% (pooled across five years) when 69-137 B and R-lines were tested in Balcarce. Regarding DLG, the only study so far performed showed a relationship between the genotypic and phenotypic variances of 54% when 31 hybrids were evaluated in Balcarce (Castaño and Giussani 2006).…”
Section: Introductionmentioning
confidence: 99%